Analisis Peramalan Tingkat Produksi Minyak Mentah (Crude Oil) Menggunakan Metode Moving Average (MA) pada PT Pertamina EP Field Sangasanga - Megawati Megawati; Anis Rachma Utary; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The goal of this research is to know the estimation rate of crude oil production that will be supplied to Refinery Unit (RU) V in Balikpapan in the upcoming period in PT Pertamina  EP  Sangasanga  Field.  The  forecast  calculation  held  during  the  appointed period and the calculation is based on the data of company history began in January 2015 until July 2016. The analysis instrument in this research is Single Moving Average method. This method is used for calculating forecast production rate in the upcoming period by using company data history. Single Moving Average method is the forecast method that use the average number (n) of the latest data to calculate the future forecast period. The result show that either forecast of each area or total of the area has different squard error. Single moving average method is appropriate in Sangasanga; Samboja, and Anggana, because either MAE or MSE of five months period is lower than three months period. For the total area, MAE of single moving average calculation of five months period is lower than three months period while the MSE of five months period is higher than three months period. However the five months period of single moving average calculation is better because even there is a little difference in MSE of total area, it is not really significance so it is still applicable as  a consideration  for  forecasting  rate production.Keywords: Moving Average, Single Moving Average, forecast, production rate, crude oil